CLARIFY OBJECT IDENTITY IN OBJECT SCHIZOPHRENIA. - Srinivas, Agneeswaran Vijay (Communications of the ACM, 2008)
A letter to the editor is presented in response to the article "Patterns, Symmetry, and Symmetry Breaking," from the March 2008 issue.